The educational leader's guide to improvement science : data, design and cases for reflection - Crow, Robert; Hinnant-Crawford, Brandi; Spaulding, Dean T. (Meyers Education Press, 2019)
"The Educational Leader's Guide to Improvement Science: Data, Design and Cases for Reflection is a collection illustrating applied organizational problem-solving using methods of improvement science in educational leadership. Early chapters introduce improvement science and then the reader is led through a logical sequence of inquiry, presented with cases of educational dilemma matched with principles of improvement science and provided examples of research methodology applied in context. Because improvement science research is so quickly becoming a signature pedagogy and core subject area of inquiry in the field of educational leadership, the literature is still scant in its coverage of improvement science models; it is the purpose of this publication to fill the void by providing concrete examples, through case studies, of instances where improvement research methods and analyses can be embedded to enhance and strengthen efforts at organizational improvement. This text concentrates on the elements faculty, students, and administrators need; specific models where improvement science frameworks enhance the reliability and validity of improvement or quality enhancement efforts. Perfect for coursessuch as: Introduction to Improvement Science, Seminar/Practicum inEducational Leadership, Introduction to Program Evaluation, EducationalResearch for Administrators, Action Research for School Practitioners, Educational Research, School Improvement, and Teacher Leadership."--